Spatial variability of soil physical attributes and agronomic characteristics of coffee grop - Carvalho, Luis Carlos Cirilo; Silva, Fábio Moreira da; Ferraz, Gabriel Araújo e Silva; Silva, Flávio Castro da; Stracieri, Juliana (Coffee Science - ISSN 1984-3909, 2014)
Precision agriculture differs from the conventional by uniting spatial relationships to the variability in the field, becoming an important management tool of the agricultural systems. Thus, the present study aimed to evaluate, by classical statistics, geoestatistics and principles of precision agriculture, some physical attributes indicative of soil compaction, such as bulk density, soil penetration resistance and clay content, and some agronomic characteristics of the coffee plant, such as height and yield. The study was conducted at Brejão farm, located in Três Pontas, MG. As data base were collected bulk density, soil resistance to penetration and clay content, at different depths, and also the height and yield of coffee plants in a 24 points irregular grid. The variables generally presented moderate to strong spatial dependence. Observing the maps of soil variables with of coffee’s variables, it was possible to note that the plant height and yield was high where bulk density, for all evaluated soil layers. There was also higher yield and plant height in regions with lower clay content and lower values of soil resistance to penetration, in all soil layers evaluated.